Complications and Mortality after CABG Surgery in Patients with Reduced Ejection Fraction - Kashchenko, Yurii V.; Sakevych, Dmytro P.; Arvanitaki, Stamatella-Ahapi S.; Rudenko, Serhii A. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Coronary artery bypass grafting (CABG) is a complex, high-tech surgical intervention. Its success depends not only on the skill and experience of the surgeon but equally on the coherence of work and professionalism of all services involved in the operation. Severe left ventricular (LV) dysfunction after heart surgery is one of the main causes of cardiogenic shock, which is characterized by a local transient reduction of myocardial contractility (“stunned” myocardium) and/or significant cell damage caused by ischemia. In this state, systemic metabolic disorders often occur: increased concentration of free fatty acids, lactic acidosis, hypoxemia, and increased catecholamine content. General approaches to determining the risk of CABG surgery have not been definitively established. In addition, the data concerning the choice of optimal tactics in patients with a reduced ejection fraction (EF) are still limited. Relatively high early operative mortality in patients with reduced left ventricular EF requires further serious study. The aim. To determine the dominant complications and causes of fatal cases in patients with reduced LV contractility after CABG surgery. Materials and methods. The study included 210 patients with EF of 35% or less, who underwent CABG at the National Amosov Institute of Cardiovascular Surgery in the period from 01/01/2015 to 12/31/2021. Among them were 190 men (90.5%) and 20 women (9.5%). The age of the patients ranged from 29 to 83 years (61.1±8.9). Most patients underwent revascularization of three or more arteries. Results and discussion. In the group of patients with EF 35-30% in the postoperative period, acute heart failure (HF) occurred in 5 (3.8%) cases, respiratory failure (RF) was observed in 3 (2.3%) cases, renal failure in 3 (2.3%) cases, central nervous system (CNS) complications in 5 (3.8%). At the same time, along with the decrease in EF, the frequency of postoperative complications increased. In patients with EF below 24%, the frequency of postoperative complications increased significantly: acute HF was noted in 3 (15%) cases, RF in 5 (25%) cases, renal failure in 2 (10%) cases, CNS complications were noted in 0 (0%) cases. The duration of artificial lung ventilation increased significantly to 24.9±27.7 hours, the length of stay in the intensive care unit increased to 12.8±8 days, and the total length of stay of the patient in the hospital to 20.2±11.7 days. Conclusion. Based on the data we received, we concluded that: in patients with reduced LV myocardial contractility, such complications as HF, RF and renal failure, CNS complications most often occur; in addition, their frequency is higher than that in patients with preserved EF and increases with its decrease; one of the most frequent and life-threatening complications in this group of patients was acute HF; the use of intra-aortic balloon pump allows to avoid or improve treatment of HF and, at the same time, to increase survival in patients with reduced LV contractility.